Polymerizable composition, cycloolefin polymer, and metal-resin composite
By using specific silane coupling agents and epoxy butene-based monomers in epoxy butene-based resins and combining fillers, the problems of increasing viscosity and decreasing adhesion after the addition of fillers are solved, and a resin system with low viscosity and high adhesion is achieved.
Patent Information
- Application Number
- JP2021537295
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-06
- Filing Date
- 2020-07-31
- Publication Date
- 2025-04-09
- Estimated Expiration
- 2040-07-31
AI Technical Summary
In the prior art, after adding filler, the viscosity of the epoxy butene-based resin is prone to increase, and the adhesion to the metal is reduced.
Using a multi-compound system containing specific epoxy butene-based monomers and silane coupling agents, the use of silane coupling agents can inhibit the increase in viscosity after the addition of fillers and improve the adhesion of epoxy butene-based resins to metals.
The low viscosity state of the epoxy butene-based resin after the filler is added is achieved, and its adhesion to metal is improved.
Smart Images

Figure 0007659496000016 
Figure 0007659496000001 
Figure 0007659496000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a polymerizable composition capable of forming a cycloolefin polymer which has low viscosity, is less likely to increase in thixotropy (viscosity at rest) even when a filler is blended therein, and has excellent adhesion to metals; a cycloolefin polymer obtained by polymerizing the polymerizable composition; and a metal resin composite in which the cycloolefin polymer is adhered to a metal. [Background technology]
[0002] Cycloolefin resins have characteristics such as excellent transparency and heat resistance, low water absorption, and low dielectric constant, and therefore have been used in a wide range of fields in recent years, such as optical components, electronic devices, medical instruments, and automobile parts.
[0003] Although cycloolefin resins have the above-mentioned excellent characteristics, they generally have poor affinity with metals, and therefore it may be difficult to obtain a cycloolefin resin molded article having excellent adhesion to metals. Therefore, Patent Document 1 proposes a polymerizable composition containing a specific cycloolefin monomer and a polymerization catalyst as a polymerizable composition capable of forming a cycloolefin resin molded article having excellent adhesion to metals. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2014 / 129486 Summary of the Invention [Problem to be solved by the invention]
[0005] However, the present inventors have conducted studies and found that the polymerizable composition described in Patent Document 1 is prone to increase in viscosity when a filler is added, and that the adhesion of the resulting cycloolefin polymer to metals may decrease.
[0006] Therefore, an object of the present invention is to provide a polymerizable composition capable of forming a cycloolefin polymer which has low viscosity, is less likely to increase in thixotropy (viscosity at rest) even when a filler is blended therein, and has excellent adhesion to metals. [Means for solving the problem]
[0007] The present inventors have discovered that by using a combination of a specific cycloolefin monomer and a specific silane coupling agent, which will be described later, as components contained in a polymerizable composition, an increase in viscosity is suppressed even when a filler is blended into the polymerizable composition, and further, the adhesion of the resulting cycloolefin polymer to metals is improved, thereby completing the present invention.
[0008] That is, according to the present invention, there is provided a polymerizable composition containing a cycloolefin monomer (α) represented by the following general formula (I) and / or a cycloolefin monomer (β) represented by the following general formula (II), a silane coupling agent having at least one hydrocarbon group having a norbornene structure, and a metathesis polymerization catalyst: [ka] (In the formula, R 1 represents a substituent selected from the group consisting of a hydrocarbon group having 1 to 10 carbon atoms, a halogen atom, and a hydrocarbon group having 1 to 10 carbon atoms substituted with a halogen atom. m represents an integer of 0 or more and 6n+6 or less. When m is 1 or more, R 1 The bonding position of R is not limited. 1 may be the same or different, and n represents an integer of 1 to 3. [ka] (In the formula, h represents an integer of 1 to 3, i and j each independently represent an integer of 0 to 4, and k represents an integer of 1 to 4.)
[0009] The polymerizable composition of the present invention preferably further contains a (meth)acrylate monomer. In the polymerizable composition of the present invention, the content ratio of the cycloolefin monomer (α) and / or the cycloolefin monomer (β) to the (meth)acrylate monomer is preferably 20 / 80 to 80 / 20 in terms of mass ratio (cycloolefin monomer / (meth)acrylate monomer). In the polymerizable composition of the present invention, the silane coupling agent is preferably a compound represented by the following general formula (III): R 2 g X p SiR 3 f (III) (In the formula, R 2 and R 3 are any groups which may be the same or different, X is a hydrocarbon group having a norbornene structure, g and f are integers of 0 to 3, p is an integer of 1 to 4, and g+f+p=4.
[0010] The polymerizable composition of the present invention preferably comprises two or more pre-mixed liquids which do not undergo a polymerization reaction by themselves, and which can form the above-mentioned polymerizable composition by combining the pre-mixed liquids.
[0011] According to the present invention, there is also provided a filler-containing polymerizable composition containing the above polymerizable composition and a filler.
[0012] In the filler-containing polymerizable composition of the present invention, the filler is preferably an inorganic filler.
[0013] According to the present invention, there is also provided a cycloolefin polymer obtained by polymerizing the above polymerizable composition or the above filler-containing polymerizable composition.
[0014] The present invention also provides a metal-resin composite in which at least a portion of the surface of the cycloolefin polymer is adhered to a metal. Effect of the Invention
[0015] According to the present invention, there can be provided a polymerizable composition capable of forming a cycloolefin polymer which has low viscosity, is less likely to increase in thixotropy (viscosity at rest) even when a filler is blended therein, and has excellent adhesion to metals. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1(A) is a plan view of a mold used to prepare a test sample for measuring adhesive strength, and FIG. 1(B) is a cross-sectional view taken along line BB in FIG. 1(A). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The polymerizable composition of the present invention contains a cycloolefin monomer (α) represented by the following general formula (I) and / or a cycloolefin monomer (β) represented by the following general formula (II), a silane coupling agent having at least one hydrocarbon group having a norbornene structure, and a metathesis polymerization catalyst. [ka] [ka]
[0018] In this specification, unless otherwise specified, the term "polymerizable composition" simply means a polymerizable composition that does not contain a filler, and the term "filler-containing polymerizable composition" means a polymerizable composition that contains a filler.
[0019] [Cycloolefin monomer (α)] In the present invention, the cycloolefin monomer (α) used as a monomer component is a compound having an alicyclic structure composed of carbon atoms in the molecule, and having a polymerizable carbon-carbon double bond and an epoxy group in the alicyclic structure. Such a cycloolefin monomer (α) contributes to the development of adhesion to metals in the obtained cycloolefin polymer.
[0020] In general formula (I), R 1 represents a substituent selected from the group consisting of a hydrocarbon group having 1 to 10 carbon atoms (preferably a hydrocarbon group having 1 to 5 carbon atoms), a halogen atom, and a hydrocarbon group having 1 to 10 carbon atoms substituted with a halogen atom (preferably a hydrocarbon group having 1 to 5 carbon atoms substituted with a halogen atom).
[0021] R 1 Examples of the hydrocarbon group having 1 to 10 carbon atoms include alkyl groups having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, and a propyl group; alkenyl groups having 2 to 10 carbon atoms, such as a vinyl group, a propenyl group, and a crotyl group; alkynyl groups having 2 to 10 carbon atoms, such as an ethynyl group, a propargyl group, and a 3-butynyl group; aryl groups having 6 to 10 carbon atoms, such as a phenyl group, a 1-naphthyl group, and a 2-naphthyl group; and cycloalkyl groups having 3 to 10 carbon atoms, such as a cyclopropyl group, a cyclopentyl group, and a cyclohexyl group.
[0022] R 1 Examples of the halogen atom include a fluorine atom, a chlorine atom, and a bromine atom.
[0023] R 1 Examples of the hydrocarbon group having 1 to 10 carbon atoms substituted with a halogen atom include a chloromethyl group, a 2-chloroethyl group, a trifluoromethyl group, and a pentafluoroethyl group.
[0024] m is an integer of 0 or more and 6n+6 or less, preferably an integer of 0 or more and 4 or less. When m is 1 or more, R 1 The bonding position of R is not limited. When m is 2 or more, 1may be the same or different. n represents an integer of 1 to 3, preferably 1 or 2, and more preferably 1.
[0025] Cycloolefin monomers (α) include 4,5-epoxytricyclo[5.2.1.0 2,6 ]dec-8-ene, 4,5-epoxy-8-chlorotricyclo[5.2.1.0 2,6 ]dec-8-ene, 4,5-epoxy-8-methyltricyclo[5.2.1.0 2,6 ]dec-8-ene, 4,5-epoxy-8-trifluoromethyltricyclo[5.2.1.0 2,6 ]Deca-8-ene, etc., compounds in which n in the general formula (I) is 1; 10,11-Epoxypentacyclo[7.4.0.1 2,5 .1 7,13 .0 8,12 ]pentadec-3-ene, 10,11-epoxy-4-chloropentacyclo[7.4.0.1 2,5 .1 7,13 .0 8,12 ]Pentadec-3-ene and other compounds in which n is 2 in formula (I); 14,15-Epoxyheptacyclo[8.7.0.1 2,9 .0 3,8 .1 4,7 .1 11,17 .0 12,16 ]Eicos-6-ene, 14,15-epoxy-5-chloroheptacyclo[8.7.0.1 2,9 .0 3,8 .1 4,7 .1 11,17 .0 12,16 ] eicos-5-ene and the like, in which n is 3 in the general formula (I);
[0026] Among them, a compound in which n is 1 is preferred because it can efficiently form the desired cycloolefin polymer. 2,6 ]deca-8-ene [also called dicyclopentadiene monoepoxide (2,3-DCPME). In this specification, it may be simply referred to as DCPME. ] is more preferred.
[0027] The content of the cycloolefin monomer (α) in the polymerizable composition of the present invention is preferably from 0.1 to 20 mass %, more preferably from 0.5 to 10 mass %, and further preferably from 1 to 5 mass %.
[0028] The cycloolefin monomer (α) used may be accompanied by a by-product generated during its synthesis. For example, when the cycloolefin monomer (α) is DCPME, 5,6-DCPME or DCPDE (dicyclopentadiene diepoxide) may be generated as a by-product. The content of the by-product in the polymerizable composition of the present invention is usually less than 1 mass%.
[0029] [Cycloolefin monomer (β)] In the present invention, the cycloolefin monomer (β) represented by the general formula (II) is a compound having an alicyclic structure composed of carbon atoms in the molecule, a polymerizable carbon-carbon double bond in the alicyclic structure, and an epoxy group-containing group bonded to the alicyclic structure. The cycloolefin monomer (β) contributes to the development of adhesion to metals in the obtained cycloolefin polymer, similar to the cycloolefin monomer (α).
[0030] In general formula (II), h represents an integer of 1 to 3, i and j each independently represent an integer of 0 to 4, and k represents an integer of 1 to 4. Preferably, i and j are each 0 or 1, and k is 2 to 4, and more preferably, i is 0, j is 0 or 1, and k is 2.
[0031] The cycloolefin monomer (β) represented by the general formula (II) is commercially available, for example, as ADEKA RESIN EP-4088S or EP-4088L (both manufactured by ADEKA Corporation).
[0032] The content of the cycloolefin monomer (β) in the polymerizable composition of the present invention is preferably from 0.1 to 20% by mass, more preferably from 0.5 to 10% by mass, and further preferably from 1 to 5% by mass.
[0033] [Other cycloolefin monomers] The polymerizable composition of the present invention preferably contains, as a monomer component, another cycloolefin monomer (hereinafter sometimes referred to as "cycloolefin monomer (γ)") which is copolymerizable with the cycloolefin monomer (α) or the cycloolefin monomer (β), has an alicyclic structure composed of carbon atoms in the molecule, and has a polymerizable carbon-carbon double bond in the alicyclic structure.
[0034] The cycloolefin monomer (γ) is a cycloolefin monomer different from the cycloolefin monomer (α) and the cycloolefin monomer (β), and may be any monomer copolymerizable with the cycloolefin monomer (α) and the cycloolefin monomer (β), and is not particularly limited. For example, norbornene monomers, monocyclic cycloolefins, etc. may be mentioned.
[0035] The norbornene-based monomer may be a compound having a norbornene structure (norbornene skeleton), and is not particularly limited thereto. Examples of the norbornene-based monomer include two-ring monomers such as norbornene and norbornadiene; three-ring monomers such as dicyclopentadiene (cyclopentadiene dimer) and dihydrodicyclopentadiene; four-ring monomers such as tetracyclododecene; five-ring monomers such as cyclopentadiene trimer; and seven-ring monomers such as cyclopentadiene tetramer.
[0036] These norbornene-based monomers may have a substituent such as an alkyl group such as a methyl group, an ethyl group, a propyl group, or a butyl group, an alkenyl group such as a vinyl group, an alkylidene group such as an ethylidene group, or an aryl group such as a phenyl group, a tolyl group, or a naphthyl group, etc. Furthermore, these norbornene-based monomers may have a polar group such as a carboxy group, an alkoxycarbonyl group, an acyloxy group, an oxy group, a cyano group, or a halogen atom.
[0037] Specific examples of such norbornene-based monomers include dicyclopentadiene, tricyclopentadiene, cyclopentadiene-methylcyclopentadiene co-dimer, 5-ethylidenenorbornene, norbornene, norbornadiene, 5-cyclohexenylnorbornene, 1,4,5,8-dimethano-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 1,4-methano-1,4,4a,5,6 ,7,8,8a-octahydronaphthalene, 6-ethylidene-1,4,5,8-dimethano-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 6-ethylidene-1,4-methano-1,4,4a,5,6,7,8,8a-octahydronaphthalene, 1,4,5,8-dimethano-1,4,4a,5,6,7,8,8a-hexahydronaphthalene, ethylene bis(5-norbornene), and the like.
[0038] The norbornene-based monomers may be used alone or in combination of two or more kinds.
[0039] Among norbornene monomers, those having a freezing point of 20° C. or higher are preferred, those having a freezing point of 28° C. or higher are more preferred, and those having a freezing point of 35° C. or higher are even more preferred, because they are easily available, have excellent reactivity, and the resulting cycloolefin polymer has excellent heat resistance. Among these, dicyclopentadiene (freezing point 31° C.) and tricyclopentadiene (freezing point 68° C.) are preferred, and dicyclopentadiene is particularly preferred, because they are easily available, have excellent reactivity, and the resulting cycloolefin polymer has excellent heat resistance.
[0040] Examples of the monocyclic cycloolefin include monocyclic cycloolefins such as cyclobutene, cyclopentene, cyclopentadiene, cyclooctene, and cyclododecene.
[0041] The content of the cycloolefin monomer (γ) in the polymerizable composition of the present invention is preferably 70% by mass or more, more preferably 80% by mass or more, and further preferably 90% by mass or more. The upper limit is about 98% by mass.
[0042] [Silane coupling agent] The silane coupling agent used in the present invention has at least one hydrocarbon group having a norbornene structure (norbornene skeleton). Since the polymerizable composition of the present invention contains such a silane coupling agent, it is possible to form a cycloolefin polymer that has low viscosity, is less likely to increase in thixotropy (viscosity at rest) even when a filler is blended, and has excellent adhesion to metals.
[0043] As the silane coupling agent having at least one hydrocarbon group having a norbornene structure, a compound represented by the following general formula (III) is preferred. R 2 g X p SiR 3 f (III)
[0044] In general formula (III), R 2 and R 3 are any groups which may be the same or different. Specific examples of the group include a hydrogen atom, a halogen atom such as a fluorine atom, a chlorine atom, or a bromine atom, an alkyl group having 1 to 6 carbon atoms such as a methyl group, an ethyl group, or a propyl group, or an alkoxy group having 1 to 6 carbon atoms such as a methoxy group, an ethoxy group, or a propoxy group, and the like. Of these, a halogen atom and an alkoxy group having 1 to 6 carbon atoms are preferred, a chlorine atom, a methoxy group, or an ethoxy group are more preferred, and a methoxy group or an ethoxy group is particularly preferred.
[0045] In the general formula (III), X is a hydrocarbon group having a norbornene structure. The total number of all carbon atoms constituting the hydrocarbon group is preferably 7 to 30, more preferably 9 to 20. Examples of the hydrocarbon group suitable for X include a bicycloheptenyl group and a bicycloheptenylalkyl group. The number of carbon atoms in the alkyl group of the bicycloheptenylalkyl group is preferably 2 to 8.
[0046] In general formula (III), g and f are integers of 0 to 3, and p is an integer of 1 to 4. In addition, g+f+p=4.
[0047] Specific examples of the compound represented by the general formula (III) include bicycloheptenyl trimethoxysilane, bicycloheptenyl triethoxysilane, bicycloheptenyl ethyl trimethoxysilane, bicycloheptenyl ethyl triethoxysilane, bicycloheptenyl hexyl trimethoxysilane, bicycloheptenyl hexyl triethoxysilane, bicycloheptenyl trichlorosilane, bicycloheptenyl ethyl trichlorosilane, bicycloheptenyl hexyl trichlorosilane, and the like. Of these, preferred are bicycloheptenyl ethyl trimethoxysilane, bicycloheptenyl ethyl triethoxysilane, bicycloheptenyl hexyl trimethoxysilane, and bicycloheptenyl hexyl triethoxysilane, more preferred are bicycloheptenyl hexyl trimethoxysilane and bicycloheptenyl ethyl triethoxysilane, and even more preferred is bicycloheptenyl ethyl trimethoxysilane.
[0048] The content of the silane coupling agent having at least one hydrocarbon group having a norbornene structure in the polymerizable composition of the present invention is preferably 0.1 to 5 mass %, more preferably 0.3 to 2 mass %, and even more preferably 0.5 to 1 mass %.
[0049] The polymerizable composition of the present invention may contain a silane coupling agent having no hydrocarbon group having a norbornene structure. Examples of such a silane coupling agent include vinyltrimethoxysilane, allyltrimethoxysilane, hexyltrimethoxysilane, acrylopropyltrimethoxysilane, and parastyryltrimethoxysilane.
[0050] The polymerizable composition of the present invention may contain a coupling agent other than the silane coupling agent. Examples of the coupling agent other than the silane coupling agent include a thiol coupling agent, an aluminate coupling agent, a titanate coupling agent, and fatty acid esters. The content of the coupling agent other than the silane coupling agent having at least one hydrocarbon group having a norbornene structure in the polymerizable composition of the present invention is usually less than 5 mass %.
[0051] [Metathesis Polymerization Catalyst] The metathesis polymerization catalyst used in the present invention is a complex in which a plurality of ions, atoms, polyatomic ions and / or compounds are bonded to a transition metal atom as a central atom. As the transition metal atom, an atom of Groups 5, 6 and 8 (long-form periodic table, the same applies below) is used. The atom of each group is not particularly limited, but an atom of Group 5 can be, for example, tantalum, an atom of Group 6 can be, for example, molybdenum or tungsten, and an atom of Group 8 can be, for example, ruthenium or osmium. Among these transition metal atoms, ruthenium and osmium of Group 8 are preferred. That is, as the metathesis polymerization catalyst used in the present invention, a complex having ruthenium or osmium as a central atom is preferred, and a complex having ruthenium as a central atom is more preferred. As the complex having ruthenium as a central atom, a ruthenium carbene complex in which a carbene compound is coordinated to ruthenium is preferred. Here, "carbene compound" is a general term for compounds having a methylene free radical, and refers to a compound having an uncharged divalent carbon atom (carbene carbon) as represented by (>C:). Ruthenium carbene complexes have excellent catalytic activity during ring-opening polymerization, so the resulting cycloolefin polymer has little odor derived from unreacted monomers, and a high-quality cycloolefin polymer can be obtained with good productivity. In addition, they are relatively stable against oxygen and moisture in the air and are not easily deactivated, so they can be used in the atmosphere. The metathesis polymerization catalyst may be used alone or in combination of multiple types.
[0052] Examples of the ruthenium carbene complex include those represented by the following general formula (1) or (2).
[0053] [ka]
[0054] In the above general formulas (1) and (2), R 4 and R 5are each independently a hydrogen atom; a halogen atom; or an organic group having 1 to 20 carbon atoms which may contain a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom, or a silicon atom; these groups may have a substituent and may be bonded to each other to form a ring. 4 and R 5 Examples of groups bonded to each other to form a ring include optionally substituted indenylidene groups such as a phenylindenylidene group.
[0055] Specific examples of the organic group having 1 to 20 carbon atoms which may contain a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom or a silicon atom include an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, an alkoxy group having 1 to 20 carbon atoms, an alkenyloxy group having 2 to 20 carbon atoms, an alkynyloxy group having 2 to 20 carbon atoms, an aryloxy group having 6 to 20 carbon atoms, an aryloxy group having 1 to 8 ... Examples of the organic groups include alkylthio groups, carbonyloxy groups, alkoxycarbonyl groups having 1 to 20 carbon atoms, alkylsulfonyl groups having 1 to 20 carbon atoms, alkylsulfinyl groups having 1 to 20 carbon atoms, alkylsulfonic acid groups having 1 to 20 carbon atoms, arylsulfonic acid groups having 6 to 20 carbon atoms, phosphonic acid groups, arylphosphonic acid groups having 6 to 20 carbon atoms, alkylammonium groups having 1 to 20 carbon atoms, and arylammonium groups having 6 to 20 carbon atoms. These organic groups having 1 to 20 carbon atoms, which may contain a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom, or a silicon atom, may have a substituent. Examples of the substituent include an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, and an aryl group having 6 to 10 carbon atoms.
[0056] X 1 and X 2 each independently represents an arbitrary anionic ligand. The anionic ligand is a ligand that has a negative charge when separated from the central metal atom, and examples of the anionic ligand include a halogen atom, a diketonate group, a substituted cyclopentadienyl group, an alkoxyl group, an aryloxy group, and a carboxyl group.
[0057] L 1 and L 2 represents a heteroatom-containing carbene compound or a neutral electron donor compound other than a heteroatom-containing carbene compound. A heteroatom-containing carbene compound and a neutral electron donor compound other than a heteroatom-containing carbene compound are compounds that have a neutral charge when separated from a central metal. From the viewpoint of improving catalytic activity, a heteroatom-containing carbene compound is preferred. The heteroatom means an atom of Groups 15 and 16 of the periodic table, and specifically includes a nitrogen atom, an oxygen atom, a phosphorus atom, a sulfur atom, an arsenic atom, and a selenium atom. Among these, from the viewpoint of obtaining a stable carbene compound, a nitrogen atom, an oxygen atom, a phosphorus atom, and a sulfur atom are preferred, and a nitrogen atom is particularly preferred.
[0058] The heteroatom-containing carbene compound is preferably a compound represented by the following general formula (3) or (4), and from the viewpoint of improving catalytic activity, a compound represented by the following general formula (3) is particularly preferred.
[0059] [ka]
[0060] In the above general formulas (3) and (4), R 6 , R 7 , R 8 and R 9 each independently represents a hydrogen atom, a halogen atom, or an organic group having 1 to 20 carbon atoms which may contain a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom, or a silicon atom. Specific examples of the organic group having 1 to 20 carbon atoms which may contain a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom, or a silicon atom are the same as those in the above general formulas (1) and (2).
[0061] Also, R 6 , R 7 , R 8 and R 9may be bonded to each other in any combination to form a ring.
[0062] In addition, since the effect of the present invention becomes more remarkable, R 8 and R 9 is preferably a hydrogen atom. 6 and R 7 is preferably an aryl group which may have a substituent, more preferably a phenyl group having an alkyl group having 1 to 10 carbon atoms as a substituent, and particularly preferably a mesityl group.
[0063] Examples of the neutral electron donor compound include oxygen atoms, water, carbonyls, ethers, nitriles, esters, phosphines, phosphinites, phosphites, sulfoxides, thioethers, amides, imines, aromatics, cyclic diolefins, olefins, isocyanides, and thiocyanates. In the above general formulas (1) and (2), R 4 , R 5 , X 1 , X 2 , L 1 and L 2 may be linked together in any combination to form multidentate chelating ligands.
[0064] As the ruthenium carbene complex used in the present invention, among the compounds represented by the above general formula (1) or (2), the compound represented by the above general formula (1) is preferred, and among these, the compound represented by the following general formula (5) or general formula (6) is more preferred.
[0065] General formula (5) is shown below. [ka]
[0066] In the above general formula (5), Z is an oxygen atom, a sulfur atom, a selenium atom, NR 15 , P.R. 15 or AsR15 and R 15 is a hydrogen atom; a halogen atom; or an organic group having 1 to 20 carbon atoms which may contain a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom, or a silicon atom; however, Z is preferably an oxygen atom because the effects of the present invention become more pronounced.
[0067] In addition, R 4 , R 5 , X 1 and L 1 are the same as those in the above general formulas (1) and (2), and may be used alone and / or may be combined with each other in any combination to form a multidentate chelating ligand, but X 1 and L 1 does not form a multidentate chelating ligand, and R 4 and R 5 are preferably bonded to each other to form a ring, are more preferably an indenylidene group which may have a substituent, and are particularly preferably a phenylindenylidene group.
[0068] Specific examples of the organic group having 1 to 20 carbon atoms which may contain a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom or a silicon atom are the same as those in the general formulae (1) and (2) above.
[0069] In the above general formula (5), R 10 and R 11 are each independently a hydrogen atom, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, or a heteroaryl group having 6 to 20 carbon atoms, and these groups may have a substituent or may be bonded to each other to form a ring. Examples of the substituent include an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, or an aryl group having 6 to 10 carbon atoms, and when a ring is formed, the ring may be any of an aromatic ring, an alicyclic ring, and a heterocyclic ring, but it is preferable to form an aromatic ring, more preferably an aromatic ring having 6 to 20 carbon atoms, and particularly preferably an aromatic ring having 6 to 10 carbon atoms.
[0070] In the above general formula (5), R 12 , R 13 and R 14 are each independently a hydrogen atom, a halogen atom, or an organic group having 1 to 20 carbon atoms which may contain a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom, or a silicon atom, and these groups may have a substituent or may be bonded to each other to form a ring. Specific examples of the organic group having 1 to 20 carbon atoms which may contain a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom, or a silicon atom are the same as those in the above general formulas (1) and (2).
[0071] R 12 , R 13 and R 14 is preferably a hydrogen atom or an alkyl group having 1 to 20 carbon atoms, and particularly preferably a hydrogen atom or an alkyl group having 1 to 3 carbon atoms.
[0072] Specific examples of the compound represented by the above general formula (5) and the production method thereof include those described in WO 03 / 062253 (JP 2005-515260 A).
[0073] General formula (6) is shown below. [ka]
[0074] In the above general formula (6), m is 0 or 1. m is preferably 1, in which case Q is an oxygen atom, a nitrogen atom, a sulfur atom, a methylene group, an ethylene group or a carbonyl group, and is preferably a methylene group.
[0075] In general formula (6), [ka] is a single bond or a double bond, preferably a single bond.
[0076] R 4, X 1 , X 2 and L 1 are the same as those in the above general formulas (1) and (2), and may be used alone and / or may be combined with each other in any combination to form a multidentate chelating ligand, but X 1 , X 2 and L 1 does not form a multidentate chelating ligand, and R 4 is preferably a hydrogen atom.
[0077] R 16 ~R 24 are each independently a hydrogen atom, a halogen atom, or an organic group having 1 to 20 carbon atoms which may contain a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom, or a silicon atom, and these groups may have a substituent or may be bonded to each other to form a ring. Specific examples of the organic group having 1 to 20 carbon atoms which may contain a halogen atom, an oxygen atom, a nitrogen atom, a sulfur atom, a phosphorus atom, or a silicon atom are the same as those in the above general formulas (1) and (2).
[0078] R 16 is preferably an alkyl group having 1 to 20 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms, and R 17 ~R 20 is preferably a hydrogen atom, R 21 ~R 24 is preferably a hydrogen atom or a halogen atom.
[0079] Specific examples of the compound represented by the above general formula (6) and a method for producing the same include those described in International Publication No. 11 / 079799 (JP Patent Publication No. 2013-516392).
[0080] As the compound represented by the above general formula (1), in addition to the compounds represented by the above general formula (5) or (6), the following compound (7) can also be suitably used. In the compound (7), PCy3 represents tricyclohexylphosphine, and Mes represents a mesityl group. [ka]
[0081] The content of the metathesis polymerization catalyst is preferably 0.005 mmol or more, more preferably 0.01 to 50 mmol, and further preferably 0.015 to 20 mmol, per 1 mol of the monomer component in the polymerizable composition.
[0082] [(Meth)acrylate Monomer] The polymerizable composition of the present invention may further contain a (meth)acrylate monomer as a monomer component in addition to the cycloolefin monomer (α) and the cycloolefin monomer (β). When the polymerizable composition of the present invention further contains a (meth)acrylate monomer, a cycloolefin polymer having even better adhesion to metals can be formed.
[0083] The (meth)acrylate monomer may be a polyfunctional monomer having three or more (meth)acryloyl groups, but a monofunctional monomer having one (meth)acryloyl group or a bifunctional monomer having two (meth)acryloyl groups is preferred, and a monofunctional monomer is more preferred. In addition, the (meth)acrylate monomer is preferably a methacrylate monomer.
[0084] The (meth)acrylate monomer preferably has a hydrocarbon group having 6 or more carbon atoms, since this provides excellent effect. The number of carbon atoms in the hydrocarbon group is preferably 6 to 100, more preferably 8 to 50, and further preferably 10 to 20.
[0085] Specific examples of monofunctional monomers having one (meth)acryloyl group include benzyl methacrylate, hexyl methacrylate, phenyl methacrylate, phenoxyethyl methacrylate, octenyl methacrylate, tolyl methacrylate, cyclohexyl methacrylate, adamantyl methacrylate, lauryl methacrylate, stearyl methacrylate, tetrahydrofurfuryl methacrylate, methoxydiethylene glycol methacrylate, dicyclopentenyloxyethyl methacrylate, and dicyclopentanyl methacrylate.
[0086] Specific examples of bifunctional monomers having two (meth)acryloyl groups include ethylene dimethacrylate, 1,3-butylene dimethacrylate, 1,4-butylene dimethacrylate, 1,6-hexanediol dimethacrylate, polyethylene glycol dimethacrylate, polyethylene glycol dimethacrylate, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, diethylene glycol dimethacrylate, bisphenol dimethacrylate, tricyclodecane dimethanol dimethacrylate, 1,3-adamantyl dimethanol dimethacrylate, 1,4-adamantyl dimethanol dimethacrylate, 2,2'-bis(4-methacryloxydiethoxyphenyl)propane, and the like.
[0087] Specific examples of polyfunctional monomers having three or more (meth)acryloyl groups include trimethylolpropane trimethacrylate and pentaerythritol trimethacrylate.
[0088] A monofunctional monomer having one (meth)acryloyl group, a bifunctional monomer having two (meth)acryloyl groups, and a polyfunctional monomer having three or more (meth)acryloyl groups may be used in any combination in any ratio.
[0089] In the polymerizable composition of the present invention, the content ratio of the cycloolefin monomer (α) and / or the cycloolefin monomer (β) to the (meth)acrylate monomer is preferably 20 / 80 to 80 / 20, more preferably 50 / 50 to 80 / 20, in terms of mass ratio (cycloolefin monomer / (meth)acrylate monomer).
[0090] [Other ingredients] The polymerizable composition of the present invention may contain other components in addition to the above-mentioned components, and such other components include activators, polymerization retarders, radical generators, modifiers, antioxidants, colorants, light stabilizers, etc. The content of these other components in the polymerizable composition of the present invention is usually less than 5%.
[0091] The activator is a compound that acts as a cocatalyst for the metathesis polymerization catalyst and improves the polymerization activity of the metathesis polymerization catalyst.The activator is not particularly limited, but specific examples thereof include organic aluminum compounds such as alkyl aluminum halides such as ethyl aluminum dichloride and diethyl aluminum chloride, and alkoxy alkyl aluminum halides; organic tin compounds such as tetrabutyl tin; organic zinc compounds such as diethyl zinc; chlorosilane compounds such as dimethyl monochlorosilane, dimethyl dichlorosilane, diphenyl dichlorosilane, tetrachlorosilane, bicycloheptenyl methyl dichlorosilane, phenyl methyl dichlorosilane, dihexyl dichlorosilane, phenyl trichlorosilane, and methyl trichlorosilane; and the like.
[0092] The polymerization retarder is used to suppress the initiation of polymerization during the preparation of a polymerizable composition by mixing a monomer component with a metathesis polymerization catalyst. Examples of such polymerization retarders include phosphines, phosphites, vinyl ether derivatives, ethers, esters, nitrile compounds, pyridine derivatives, alcohols, acetylenes, and α-olefins.
[0093] The radical generator includes known organic peroxides, diazo compounds, non-polar radical generators, etc. Among them, organic peroxides are preferred.
[0094] Examples of organic peroxides include hydroperoxides such as t-butyl hydroperoxide and cumene hydroperoxide; dialkyl peroxides such as di-t-butyl peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)-3-hexyne and 2,5-dimethyl-2,5-di(t-butylperoxy)hexane; etc. Dialkyl peroxides are preferred because they cause less hindrance to the metathesis polymerization reaction.
[0095] The polymerizable composition of the present invention may be composed of two or more premixed liquids that do not cause a polymerization reaction by themselves, and the above-mentioned polymerizable composition may be formed by combining the premixed liquids. That is, the present invention also relates to a combination of two or more premixed liquids for forming the above-mentioned polymerizable composition, in which each premixed liquid has a composition that does not cause a polymerization reaction by itself, and the above-mentioned polymerizable composition can be formed by mixing the premixed liquids.
[0096] The two or more pre-mixed liquids can be prepared by selecting the above-mentioned components so that each pre-mixed liquid does not cause a polymerization reaction to proceed alone, but can form the above-mentioned polymerizable composition by mixing them.
[0097] The two or more pre-blended liquids are preferably prepared by the following two methods, depending on whether the metathesis polymerization catalyst used requires an activator (cocatalyst) or not.
[0098] When the metathesis polymerization catalyst used does not require an activator, it is preferable to prepare a two-liquid type polymerizable composition consisting of a premixed liquid (i) containing a monomer component and a premixed liquid (ii) containing a metathesis polymerization catalyst. The premixed liquid (ii) can be prepared, for example, by dissolving or dispersing the metathesis polymerization catalyst in a small amount of a suitable solvent. Examples of the solvent include aromatic hydrocarbons such as toluene, xylene, ethylbenzene, and trimethylbenzene; and ketones such as methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, and 4-hydroxy-4-methyl-2-pentanone.
[0099] When the metathesis polymerization catalyst requires an activator, it is preferable to prepare a two-liquid type polymerizable composition consisting of a premixed liquid (hereinafter sometimes referred to as "liquid A") containing a monomer component and a metathesis polymerization catalyst, and a premixed liquid (hereinafter sometimes referred to as "liquid B") containing a monomer component and an activator. In this case, a three-liquid type polymerizable composition consisting of liquids A and B and a premixed liquid (hereinafter sometimes referred to as "liquid C") consisting of only a monomer component may be prepared.
[0100] Components other than the metathesis polymerization catalyst, activator, and monomer component may be blended in any pre-blended liquid.
[0101] [Filler] The polymerizable composition of the present invention can be used by blending a filler. Since the polymerizable composition of the present invention is unlikely to increase in viscosity or thixotropy (viscosity at rest) even when a filler is blended, it is possible to blend a large amount of filler. According to the filler-containing polymerizable composition of the present invention obtained by blending a filler with the polymerizable composition of the present invention, a cycloolefin-based polymer having excellent adhesion to metals can be formed, similarly to the polymerizable composition of the present invention.
[0102] The filler may be either an inorganic filler or an organic filler, with inorganic fillers being preferred, and a combination of inorganic and organic fillers may also be used.
[0103] Examples of inorganic fillers include particulate fillers with an aspect ratio of 1 to 2. Specific examples of inorganic fillers include calcium carbonate, calcium hydroxide, calcium silicate, calcium sulfate, aluminum hydroxide, magnesium hydroxide, titanium oxide, zinc oxide, barium titanate, silica, alumina, carbon black, graphite, fullerene, antimony oxide, red phosphorus, various metal powders, clay, various ferrites, hydrotalcite, etc. Among these, silica, alumina, and aluminum hydroxide are preferred because they do not inhibit the ring-opening polymerization reaction.
[0104] Examples of organic fillers include fibrous fillers with an aspect ratio of 5 or more. Specific examples of organic fillers include glass fibers, carbon fibers, wollastonite, potassium titanate, zonolite, basic magnesium sulfate, aluminum borate, tetrapod-type zinc oxide, gypsum fibers, phosphate fibers, alumina fibers, acicular calcium carbonate, acicular boehmite, etc. Examples of glass fibers that can be suitably used include E-glass, NE-glass, S-glass, D-glass, and H-glass fibers. The filler may be either an inorganic filler or an organic filler, such as a bromine-based flame retardant.
[0105] The filler may have its surface hydrophobized. By using a hydrophobized filler, the filler can be prevented from flocculating or settling in the filler-containing polymerizable composition, and the filler can be uniformly dispersed in the resulting cycloolefin polymer. Examples of the treatment agent used for the hydrophobization include silane coupling agents such as vinyltrimethoxysilane, titanate coupling agents, aluminate coupling agents, fatty acids such as stearic acid, oils and fats, surfactants, waxes, etc. The filler can also be hydrophobized by simultaneously mixing the treatment agent with the filler when preparing the filler-containing polymerizable composition.
[0106] The amount of the filler in the filler-containing polymerizable composition is preferably 10 to 1000 parts by mass, more preferably 100 to 500 parts by mass, based on 100 parts by mass of the polymerizable composition of the present invention. By setting the amount of the filler in the above range, the strength of the obtained cycloolefin polymer can be increased.
[0107] [Method of preparing polymerizable composition] The polymerizable composition of the present invention can be obtained by mixing the above-mentioned components.The mixing method may be according to a conventional method, for example, a liquid (catalyst liquid) is prepared by dissolving or dispersing a metathesis polymerization catalyst and, if necessary, a polymerization reaction retarder, etc. in a suitable solvent, a liquid (monomer liquid) is prepared by separately mixing a cycloolefin monomer (α) and / or a cycloolefin monomer (β) and other components, and the catalyst liquid is added to the monomer liquid and stirred to prepare the composition.
[0108] The solvent used for preparing the catalyst solution or the monomer solution is not particularly limited. For example, the solvent may be a chain aliphatic hydrocarbon such as n-pentane, n-hexane, n-heptane, liquid paraffin, or mineral spirit; an alicyclic hydrocarbon such as cyclopentane, cyclohexane, methylcyclohexane, dimethylcyclohexane, trimethylcyclohexane, ethylcyclohexane, diethylcyclohexane, decahydronaphthalene, dicycloheptane, tricyclodecane, hexahydroindene, or cyclooctane; an aromatic hydrocarbon such as benzene, toluene, or xylene; a hydrocarbon having an alicyclic ring and an aromatic ring such as indene or tetrahydronaphthalene; a nitrogen-containing hydrocarbon such as nitromethane, nitrobenzene, or acetonitrile; an oxygen-containing hydrocarbon such as diethyl ether or tetrahydrofuran; an aromatic hydrocarbon such as toluene, xylene, ethylbenzene, or trimethylbenzene; a ketone such as methyl ethyl ketone, cyclopentanone, cyclohexanone, 2-heptanone, or 4-hydroxy-4-methyl-2-pentanone; or the like.
[0109] The polymerizable composition of the present invention may be solidified by cooling. "Solidification by cooling" means solidification under cooling. Such a polymerizable composition can be prepared, for example, by the following two methods.
[0110] In the first method, a monomer component previously cooled below its freezing point to be solidified, a metathesis polymerization catalyst, the silane coupling agent, and other optional components added as desired are mixed while cooling at a temperature at which the monomer component does not substantially melt, and the resulting mixture is pressurized and cooled using, for example, a tablet machine or a press molding machine to solidify the mixture, thereby preparing a polymerizable composition. The temperature at which each component is mixed depends on the monomer component used, but is usually preferably 25°C or lower.
[0111] In the second method, a liquid monomer component, a metathesis polymerization catalyst, the silane coupling agent, and other optional components added as desired are mixed at a temperature at which the resulting mixture remains liquid, and before the ring-opening polymerization of the monomer component substantially proceeds, the mixture is cooled and solidified, for example, using a mold described below, to prepare a polymerizable composition. The temperature at which each component is mixed varies depending on the monomer component used, but is usually preferably 30 to 60°C.
[0112] In any of the methods, the cooling temperature for cooling and solidifying is usually preferably −60 to 0° C., although it depends on the monomer component used. By blending a filler as the optional component, it is also possible to obtain a filler-containing polymerizable composition that is cooled and solidified.
[0113] [Cycloolefin polymer] The cycloolefin polymer of the present invention is obtained by polymerizing the polymerizable composition of the present invention or the filler-containing polymerizable composition (hereinafter, both may be collectively referred to simply as "polymerizable composition".) Since the polymerizable composition of the present invention contains a metathesis polymerization catalyst, the cycloolefin polymer is obtained by a metathesis ring-opening polymerization reaction.
[0114] The reaction form of the metathesis ring-opening polymerization reaction is not particularly limited, and examples thereof include solution polymerization and bulk polymerization. Among them, bulk polymerization reaction is preferred because it can efficiently produce a cycloolefin polymer. Details of the bulk polymerization reaction will be described in the section "Cycloolefin resin molded product".
[0115] When the ring-opening polymerization reaction is carried out by solution polymerization, the solvent to be used is not particularly limited, but a hydrocarbon solvent is preferred. Examples of the hydrocarbon solvent include aromatic hydrocarbons such as benzene, toluene, and xylene; chain aliphatic hydrocarbons such as n-pentane, hexane, and heptane; and alicyclic hydrocarbons such as cyclopentane, cyclohexane, and cyclooctane. Among them, aromatic hydrocarbons and alicyclic hydrocarbons are preferred, toluene, cyclohexane, and cyclooctane are more preferred, and toluene and cyclohexane are particularly preferred. These hydrocarbon solvents can be used alone or in combination of two or more.
[0116] In the solution polymerization, the polymerization temperature is not particularly limited, but is usually −30 to 150° C., and preferably −10 to 120° C. The polymerization time is not particularly limited, but is usually 1 minute to 100 hours.
[0117] The weight average molecular weight (Mw) of the cycloolefin polymer of the present invention varies depending on the application, but is usually 5,000 to 500,000, more preferably 10,000 to 100,000. This value is a polystyrene-equivalent value measured by gel permeation chromatography using tetrahydrofuran as a solvent.
[0118] The glass transition temperature (Tg) of the cycloolefin polymer of the present invention is usually from 120 to 200°C, and preferably from 140 to 180°C.
[0119] The cycloolefin polymer of the present invention has an epoxy group derived from a cycloolefin monomer (α) or a cycloolefin monomer (β) and has excellent affinity with metals. The cycloolefin polymer of the present invention is preferably used as a material for forming a cycloolefin resin molded article or a metal-resin composite described later.
[0120] [Cycloolefin-based resin molded body] According to the present invention, it is possible to provide a cycloolefin resin molded article containing a cycloolefin polymer obtained by polymerizing the polymerizable composition or the filler-containing polymerizable composition of the present invention.
[0121] Examples of methods for producing cycloolefin-based resin molded articles include (a) a method in which a polymerizable composition is applied onto a support, followed by bulk polymerization, (b) a method in which a polymerizable composition is poured into a mold, followed by bulk polymerization, and (c) a method in which a fibrous reinforcing material is impregnated with the polymerizable composition, followed by bulk polymerization.
[0122] Examples of the support used in method (a) include films or plates made of resins such as polytetrafluoroethylene, polyethylene terephthalate, polypropylene, polyethylene, polycarbonate, polyethylene naphthalate, polyarylate, and nylon; foils or plates made of metal materials such as iron, stainless steel, copper, aluminum, nickel, chromium, gold, and silver; etc. Among these, the use of metal foils or resin films is preferred.
[0123] From the viewpoint of workability and the like, the thickness of the metal foil or resin film is usually 1 to 200 μm, preferably 1 to 150 μm, more preferably 6 to 125 μm, and further preferably 12 to 100 μm.
[0124] The metal foil preferably has a smooth surface, and the surface roughness (Rz) measured by AFM (atomic force microscope) is usually 10 μm or less, preferably 5 μm or less, and more preferably 3 μm or less.
[0125] Examples of a method for applying the polymerizable composition of the present invention onto a support include known application methods such as spray coating, dip coating, roll coating, curtain coating, die coating, and slit coating.
[0126] The polymerizable composition applied on the support is dried as desired, and then bulk polymerized. The bulk polymerization may be carried out at room temperature, or may be carried out by heating the polymerizable composition to a predetermined temperature. The method for heating the polymerizable composition is not particularly limited, and examples thereof include a method in which the polymerizable composition applied on the support is placed on a heating plate and heated, a method in which the composition is heated while being pressed using a press (heat pressing), a method in which the composition is pressed with a heated roller, and a method in which the composition is heated in a heating furnace.
[0127] According to the method (a), a cycloolefin resin molded product with a support can be obtained in the form of a film, a plate, etc. The thickness of the cycloolefin resin molded product is usually 15 mm or less, preferably 5 mm or less, more preferably 0.5 mm or less, and most preferably 0.1 mm or less.
[0128] In the method (b), it is preferable to use a polymerizable composition consisting of two or more pre-blended liquids.
[0129] Examples of the method of injecting a polymerizable composition into the cavity of a mold and then bulk polymerizing the composition include the RIM method, the RTM method, the potting method, the (solid, liquid) transfer molding method, the compression molding method, the print molding method, the vacuum casting method, etc. Hereinafter, the RIM method, which is preferably used when the polymerizable composition is in a liquid state, will be described.
[0130] In the RIM molding method, a known impingement mixer is usually used as a reaction injection molding (RIM) device to bulk polymerize a polymerizable composition in a mold. For example, when two or more premixed liquids [premixed liquid (i) and premixed liquid (ii), or "liquid A", "liquid B" and "liquid C"] are introduced separately into the impingement mixer, they are instantly mixed in a mixing head to prepare a polymerizable composition, which is then injected directly into a mold, heated in the mold to cause bulk polymerization, and a cycloolefin resin molded body is obtained. It is also possible to use a low-pressure injection machine such as a dynamic mixer or a static mixer instead of the impingement mixer.
[0131] The mold is not particularly limited, but it is preferable to use a mold having a split mold structure formed of a male mold and a female mold. The mold used does not necessarily need to be an expensive mold with high rigidity, and a mold made of resin or the like can be used. The material of the mold is not particularly limited, but examples thereof include steel, aluminum, zinc alloy, nickel, copper, chromium, etc., and may be manufactured by any method such as casting, forging, spraying, electroforming, etc., or may be plated.
[0132] After the bulk polymerization is completed, the mold is opened and the product is demolded to obtain a cycloolefin resin molded product.
[0133] According to the method (b), a cycloolefin resin molded product can be obtained in any shape, such as a sheet, a film, a column, a cylinder, or a polygonal column.
[0134] Examples of the fibrous reinforcing material used in the method (c) include organic fibers such as PET (polyethylene terephthalate) fibers, aramid fibers, ultra-high molecular weight polyethylene fibers, polyamide (nylon) fibers, and liquid crystal polyester fibers, as well as inorganic fibers such as tungsten fibers, molybdenum fibers, titanium fibers, steel fibers, boron fibers, silicon carbide fibers, and silica fibers. Among these, organic fibers are preferred, and aramid fibers and liquid crystal polyester fibers are particularly preferred. These can be used alone or in combination of two or more. The form of the fibrous reinforcing material is not particularly limited, and examples thereof include mats, cloths, and nonwoven fabrics.
[0135] Examples of methods for impregnating a fibrous reinforcing material with the polymerizable composition include a method in which a predetermined amount of the polymerizable composition is applied to the fibrous reinforcing material by a known method such as spray coating, dip coating, roll coating, curtain coating, die coating, or slit coating, and if desired, a protective film is placed on top of the applied composition, and the applied composition is pressed from above with a roller or the like.
[0136] After the polymerizable composition is impregnated into a fibrous reinforcing material, the polymerizable composition can be bulk polymerized at room temperature or by heating the impregnated material to a predetermined temperature, thereby obtaining a desired cycloolefin resin molded product.
[0137] The content of the fibrous reinforcing material in the cycloolefin resin molded product is usually in the range of 10 to 90 mass %, preferably 20 to 80 mass %, and more preferably 30 to 70 mass %.
[0138] Examples of a method for heating the impregnated product obtained by impregnating a fibrous reinforcing material with a polymerizable composition include a method in which the impregnated product is placed on a support and heated as in method (a), and a method in which a fibrous reinforcing material is placed in a mold in advance, the polymerizable composition is impregnated in the mold to obtain an impregnated product, and the impregnated product is heated as in method (b).
[0139] According to the method (c), a sheet-like or film-like cycloolefin resin molded article having a fibrous reinforcing material can be obtained. The thickness of the obtained cycloolefin resin molded article is usually in the range of 0.001 to 10 mm, preferably 0.005 to 1 mm, and more preferably 0.01 to 0.5 mm.
[0140] In any of the methods (a), (b) and (c), the temperature for polymerizing the polymerizable composition is usually in the range of 10 to 250° C., preferably 10 to 200° C., and more preferably 10 to 150° C. The polymerization time may be appropriately selected, but is usually 1 second to 20 minutes, and preferably 10 seconds to 5 minutes. By polymerizing the polymerizable composition under such conditions, a cycloolefin resin molded product with a small amount of unreacted monomer can be obtained.
[0141] The cycloolefin-based resin molded article is obtained by polymerizing the polymerizable composition or the filler-containing polymerizable composition of the present invention, similarly to the cycloolefin-based polymer, and therefore has excellent adhesion when pressed against a metal material, and is therefore preferably used as a material for forming a metal-resin composite.
[0142] The above-mentioned cycloolefin polymer and cycloolefin resin molded article can be obtained by a single polymerization reaction. From the viewpoint of further improving heat resistance and adhesion to metal, the obtained cycloolefin polymer or cycloolefin resin molded article may be further heated after polymerizing the polymerizable composition.
[0143] That is, the cycloolefin polymer or cycloolefin resin molded body can be obtained, for example, by a method including a step of primarily curing a polymerizable composition and a step of heating the cured product obtained by the primary curing to secondary cure.
[0144] The primary curing may be carried out at room temperature or by heating the polymerizable composition. The temperature for the primary curing is usually in the range of 10 to 100° C., preferably 10 to 80° C., and more preferably 10 to 60° C. The time required for the primary curing is usually 1 second to 60 minutes, and preferably 10 seconds to 40 minutes.
[0145] The heating temperature in the secondary curing is usually more than 100° C. and less than 350° C., preferably 110 to 330° C., and more preferably 120 to 310° C. The heating time for the secondary curing is usually 10 to 120 minutes, preferably 20 to 90 minutes, and more preferably 30 to 60 minutes.
[0146] [Metal resin composite] The metal-resin composite of the present invention is formed by polymerizing the polymerizable composition or filler-containing polymerizable composition of the present invention, and at least a part of the surface of the cycloolefin polymer is in close contact with a metal.
[0147] The metal-resin composite of the present invention can be produced by polymerizing the polymerizable composition of the present invention adjacent to a metal. The metal may be a metal substrate such as a metal foil (Aspect 1). The metal substrate may be the same as the metal foil exemplified as the support in the above-mentioned "Method (a)". In addition, since the cycloolefin polymer of the present invention can be suitably used as a sealing material for electronic devices, the metal may be a metal to be sealed in an electronic device, such as a metal wire or metal wiring (Aspect 2).
[0148] The metal-resin composite of the above-mentioned aspect 1 can be obtained, for example, by using a metal foil or the like as the support in the above-mentioned method (a).
[0149] The metal resin composite of the above embodiment 2 can be obtained, for example, in the above method (b) by placing an electronic device in a mold in advance, injecting a polymerizable composition into the mold, and heating the mold.
[0150] The metal-resin composite of the present invention can also be obtained by overlapping a sheet-shaped cycloolefin resin molded body containing the cycloolefin polymer obtained by any of the above methods (a) to (c) with a metal substrate or a metal to be sealed in an electronic device such that the resin portion of the cycloolefin resin molded body faces the metal substrate or the metal to be sealed in an electronic device, and then hot pressing the overlapping bodies.
[0151] The pressure during the heat pressing is usually 0.5 to 20 MPa, preferably 1 to 10 MPa. The heat pressing may be performed in a vacuum or reduced pressure atmosphere. The heat pressing may be performed using a known press machine having a press frame for plate molding, or a press molding machine such as a sheet mold compound (SMC) or bulk mold compound (BMC) press.
[0152] The metal-resin composite of the present invention may have one or more metal layers, and may have one or more layers of a sheet-shaped cycloolefin-based resin molded product containing a cycloolefin-based polymer.
[0153] When the metal resin composite of the present invention is in the form of a sheet, its thickness is not particularly limited, but is usually from 1 μm to 10 mm.
[0154] The cycloolefin resin molded articles and metal resin composites obtained as described above can be used for, for example, automotive applications such as bumpers and air deflectors, construction and industrial machinery applications such as wheel loaders and power shovels, leisure applications such as golf carts and game machines, medical applications such as medical equipment, industrial applications such as large panels and chairs, housing equipment applications such as shower pans and wash basins, and electrical insulation applications such as electrical insulating structures as an electrical insulating sealant.
[0155] The metal-resin composite of the present invention is a cycloolefin polymer obtained by polymerizing the polymerizable composition or filler-containing polymerizable composition of the present invention, in which at least a part of the surface thereof is adhered to a metal, and has excellent adhesion between the metal and the cycloolefin polymer. Because the metal-resin composite of the present invention has such properties, it is particularly suitable for use as a printed circuit board material such as resin-coated copper (RCC) and copper clad laminates (CCL); and as a sealing part for electronic devices such as coils, pumps, motors, molded transformers, semiconductors, power modules, capacitors, and electronic boards such as circuit boards for communication and electronics. EXAMPLES
[0156] The present invention will be specifically described below with reference to examples and comparative examples. In the following, "parts" are by mass unless otherwise specified. The tests and evaluations were performed as follows.
[0157] Example 1 (Preparation of Monomer Mixture) A monomer mixture having the composition shown in Table 1 was prepared by mixing RIM monomer (manufactured by Zeon Corporation), dicyclopentadiene monoepoxide (DCPME), and bicycloheptenylethyltrimethoxysilane. DCPME was used as a cyclopentanone solution (DCPME content: about 40% by mass, by-product content: about 27% by mass) containing 5,6-DCPME and DCPDE as by-products (hereinafter the same). The RIM monomer contains 90 parts of dicyclopentadiene and 10 parts of tricyclopentadiene as cycloolefin monomers.
[0158] [ka]
[0159] (Preparation of catalyst solution) A catalyst solution was obtained by dissolving 0.3 parts of a ruthenium catalyst (Zhan1N) represented by the formula (8) as a metathesis polymerization catalyst, 39.7 parts of 2,6-di-t-butyl-p-cresol (BHT, antioxidant), and 30 parts of triphenylphosphine in 30 parts of cyclopentanone.
[0160] [ka] (In the formula, Mes represents a mesityl group.)
[0161] (Preparation of Polymerizable Composition) To 100 parts of the monomer mixture heated to 40° C., 3.5 parts of the catalyst solution was added, and the mixture was mixed to prepare a polymerizable composition.
[0162] (Viscosity measurement) The polymerizable composition and silica (MLR-1114, manufactured by Tatsumori Co., Ltd.) were mixed as a filler to prepare a filler-containing polymerizable composition containing 15.0% by mass of the polymerizable composition and 85.0% by mass of silica. The viscosity of the filler-containing polymerizable composition was determined by measuring the value when the liquid temperature was set to 30°C and the No. 23 rotor was used to stir for 1 minute at a rotation speed of 100 rpm or 10 rpm using a B-type viscometer. In addition, the ratio of the viscosity at a rotation speed of 10 rpm to the viscosity at a rotation speed of 100 rpm was calculated. The thixotropy can be calculated from the magnitude of the ratio. The results are shown in Table 1.
[0163] (Adhesive strength measurement) As shown in FIG. 1, a Teflon (registered trademark) plate 11 having a truncated cone-shaped hole 21 was placed on a nickel substrate 12 to prepare a mold having a truncated cone-shaped cavity (bottom diameter 3.53 mm, top diameter 3.00 mm, height 3.00 mm). A filler-containing polymerizable composition was poured into the truncated cone-shaped cavity at room temperature, and the filler-containing polymerizable composition was allowed to harden naturally (primary hardening). After the primary hardening, the filler-containing polymerizable composition was further hardened by heating at 150° C. for 1 hour (secondary hardening). After the secondary hardening, the Teflon (registered trademark) plate was removed to prepare a test sample in which a cycloolefin-based polymer formed from the filler-containing polymerizable composition was adhered to the nickel substrate.
[0164] The adhesive strength between the cycloolefin polymer of the test sample and the nickel substrate was measured five times in total using a tensile tester at a crosshead speed of 0.1 mm / min, and the average value of the five measured values was calculated. The results are shown in Table 1.
[0165] Example 2 Except for changing the substrate used in measuring the adhesive strength from a nickel substrate to a copper substrate, a test sample was prepared and the adhesive strength was measured in the same manner as in Example 1. The results are shown in Table 1.
[0166] Example 3 (Preparation of Monomer Mixture) A RIM monomer (manufactured by Zeon Corporation), dicyclopentadiene monoepoxide (DCPME) and bicycloheptenylethyltrimethoxysilane were mixed to prepare a monomer mixture having the composition shown in Table 1. The composition of the RIM monomer was the same as that in Example 1.
[0167] (Preparation of catalyst solution) A catalyst solution was obtained by dissolving 0.3 parts of a ruthenium catalyst (Zhan1N) represented by the formula (8) as a metathesis polymerization catalyst, 39.7 parts of 2,6-di-t-butyl-p-cresol (BHT, antioxidant), and 30 parts of triphenylphosphine in 30 parts of cyclopentanone.
[0168] (Preparation of Polymerizable Composition) To 100 parts of the monomer mixture heated to 40° C., 3.5 parts of the catalyst solution was added, and the mixture was mixed to prepare a polymerizable composition.
[0169] (Viscosity measurement) The polymerizable composition and silica (MLR-1114, manufactured by Tatsumori Co., Ltd.) as a filler were mixed to prepare a filler-containing polymerizable composition containing 30.0% by mass of the polymerizable composition and 70.0% by mass of silica. The viscosity was measured in the same manner as in Example 1, except that the obtained filler-containing polymerizable composition was used. The results are shown in Table 1.
[0170] (Adhesive strength measurement) Except for using the filler-containing polymerizable composition prepared as above, a test sample was prepared and the adhesive strength was measured in the same manner as in Example 1. The results are shown in Table 1.
[0171] Example 4 Except for changing the substrate used in measuring the adhesive strength from a nickel substrate to a copper substrate, a test sample was prepared and the adhesive strength was measured in the same manner as in Example 3. The results are shown in Table 1.
[0172] Comparative Examples 1 and 2 A monomer mixture having the composition shown in Table 1 was prepared in the same manner as in Examples 3 and 4, except that vinyl silane (vinyl trimethoxy silane (KBM-1003) manufactured by Shin-Etsu Chemical Co., Ltd.) was used instead of bicycloheptenylethyl trimethoxy silane. A polymerizable composition and a filler-containing polymerizable composition were prepared and their viscosity and adhesive strength were measured in the same manner as in Examples 3 and 4, except that a monomer mixture having the composition shown in Table 1 was used. The results are shown in Table 1.
[0173] Comparative Examples 3 and 4 A monomer mixture having the composition shown in Table 1 was prepared in the same manner as in Examples 3 and 4, except that bicycloheptenylethyltrimethoxysilane was not used. A polymerizable composition and a filler-containing polymerizable composition were prepared in the same manner as in Examples 3 and 4, except that a monomer mixture having the composition shown in Table 1 was used, and the viscosity and adhesive strength were measured. The results are shown in Table 1.
[0174] [Table 1]
[0175] From Table 1, it can be seen that the polymerizable composition containing the cycloolefin monomer represented by the general formula (I), the silane coupling agent having at least one hydrocarbon group having a norbornene structure, and the metathesis polymerization catalyst has a low viscosity and does not increase the thixotropy (viscosity at rest) even when a large amount of filler is blended. Moreover, it can be seen that by using such a polymerizable composition, a cycloolefin polymer having excellent adhesion to metal can be obtained (Examples 1 to 4). On the other hand, when a silane coupling agent not having a hydrocarbon group with a norbornene structure was used, or when no silane coupling agent was used, the viscosity of the polymerizable composition was high, the thixotropy (viscosity at rest) increased, and the adhesion of the resulting cycloolefin polymer to metals was poor (Comparative Examples 1 to 4).
Claims
1. A filler-containing polymerizable composition obtained by blending a filler with a polymerizable composition containing a cycloolefin monomer (α) represented by the following general formula (I) and / or a cycloolefin monomer (β) represented by the following general formula (II), a silane coupling agent having at least one hydrocarbon group having a norbornene structure, a (meth)acrylate monomer, and a metathesis polymerization catalyst: 【Chemistry 13】 (In the formula, R 1 represents a substituent selected from the group consisting of a hydrocarbon group having 1 to 10 carbon atoms, a halogen atom, and a hydrocarbon group having 1 to 10 carbon atoms substituted with a halogen atom. m represents an integer of 0 or more and 6n+6 or less. When m is 1 or more, R 1 When m is 2 or more, R 1 may be the same or different. n represents an integer of 1 to 3. 【Chemistry 14】 (In the formula, h represents an integer of 1 to 3, i and j each independently represent an integer of 0 to 4, and k represents an integer of 1 to 4.)
2. The filler-containing polymerizable composition according to claim 1, wherein a content ratio of the cycloolefin monomer (α) and / or the cycloolefin monomer (β) to the (meth)acrylate monomer is 20 / 80 to 80 / 20 in terms of a mass ratio (cycloolefin monomer / (meth)acrylate monomer).
3. 3. The filler-containing polymerizable composition according to claim 1, wherein the silane coupling agent is a compound represented by the following general formula (III): R 2 g X p SiR 3 f (III) (In the formula, R 2 and R 3 are any groups which may be the same or different, X is a hydrocarbon group having a norbornene structure, g and f are integers of 0 to 3, p is an integer of 1 to 4, and g+f+p=4.
4. 4. The filler-containing polymerizable composition according to claim 1, which comprises two or more premixed liquids which do not undergo polymerization reaction by themselves.
5. 5. The filler-containing polymerizable composition according to claim 1, wherein the filler is an inorganic filler.
6. A cycloolefin polymer obtained by polymerizing the filler-containing polymerizable composition according to any one of claims 1 to 5.
7. 7. A metal-resin composite comprising the cycloolefin polymer according to claim 6, at least a part of the surface of which is in close contact with a metal.
Citation Information
Patent Citations
Cycloolefin composition
JP2000309629A
Photoresist compositions comprising polycyclic polymers having acid-labile pendant groups
JP2001516780A
Optical waveguide and optical waveguide structure
JP2006323244A
Optical element mounting component and optical element mounted component
JP2008158474A
Composite mold
JP2009255380A